First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Reply to comment: How are single-shot photographs orthorectified?: comment on “Quantifying sponge communities from shallow to mesophotic depths using orthorectified imagery” (Lesser et al. 2023) - M. P. Lesser; M. Slattery (Marine Biology, 2024)

Phylosymbiosis and metabolomics resolve phenotypically plastic and cryptic sponge species in the genus Agelas across the Caribbean basin - M. S. Pankey; D. J. Gochfeld; M. Gastaldi; K. J. Macartney; A. Clayshulte Abraham; M. Slattery; M. P. Lesser (Molecular Ecology, 2024)
Fundamental to holobiont biology is recognising how variation in microbial composition and function relates to host phenotypic variation. Sponges often exhibit considerable phenotypic plasticity and also harbour dense microbial communities that function to protect and nourish hosts. One of the most prominent sponge genera on Caribbean coral reefs is Agelas . Using a comprehensive set of morphological (growth form, spicule), chemical and molecular data on 13 recognised species of Agelas in the Caribbean basin, we were able to define only five species (=clades) and found that many morphospecies designations were incongruent with phylogenomic and population genetic analyses. Microbial communities were also strongly differentiated between phylogenetic species, showing little evidence of cryptic divergence and relatively low correlation with morphospecies assignment. Metagenomic analyses also showed strong correspondence to phylogenetic species, and to a lesser extent, geographical and morphological characters. Surprisingly, the variation in secondary metabolites produced by sponge holobionts was explained by geography and morphospecies assignment, in addition to phylogenetic species, and covaried significantly with a subset of microbial symbionts. Spicule characteristics were highly plastic, under greater impact from geographical location than phylogeny. Our results suggest that while phenotypic plasticity is rampant in Agelas , morphological differences within phylogenetic species affect functionally important ecological traits, including the composition of the symbiotic microbial communities and metabolomic profiles.

Trophodynamics of the sclerosponge Ceratoporella nicholsoni along a shallow to mesophotic depth gradient - Keir J. Macartney; M. Sabrina Pankey; Marc Slattery; Michael P. Lesser (Coral Reefs, 2020)

A New “Business as Usual” Climate Scenario and the Stress Response of the Caribbean Coral Montastraea cavernosa - Michael P. Lesser; Jessica K. Jarett; Cara L. Fiore; Megan M. Thompson; M. Sabrina Pankey; Keir J. Macartney (Frontiers in Marine Science, 2020)

Depth‐dependent detritus production in the sponge, Halisarca caerulea - Michael P. Lesser; Benjamin Mueller; M. Sabrina Pankey; Keir J. Macartney; Marc Slattery; Jasper M. de Goeij (Limnology and Oceanography, 2020)
Sponges are important ecological and functional components of coral reefs. Recently, a new hypothesis about the functional ecology of sponges in organic matter recycling pathways, the sponge‐loop hypothesis, in which dissolved and particulate organic matter is taken up by sponges and shunted to higher trophic levels as detritus, has been proposed and demonstrated for shallow ( Halisarca caerulea from water depths of 10 and 50 m. Detritus production was significantly lower in mesophotic sponges compared to shallow samples of H. caerulea . Additionally, detritus production rates in transplanted sponges moved in the direction of rates observed for resident conspecifics. The microbiome of these sponge populations was also significantly different between shallow and mesophotic depths, and the microbial communities of the transplanted sponges also shifted in the direction of their new depth in 10 d largely driven by changes in Oxyphotobacteria , Acidimicrobiia , Nitrososphaeria , Nitrospira , Deltaproteobacteria , and Dadabacteriia . This occurred in an environment where the availability of both dissolved and particulate trophic resources changed significantly across the shallow to mesophotic depth gradient where these sponge populations were found. These results suggest that changes in sponge detritus production are primarily driven by differential quality and quantity of trophic resources, as well as their utilization by the sponge host, and its microbiome, along the shallow to mesophotic depth gradient.

N2 fixation, and the relative contribution of fixed N, in corals from Curaçao and Hawaii - Michael P. Lesser; Kathleen M. Morrow; M. Sabrina Pankey (Coral Reefs, 2019)

Aposematic coloration does not deter corallivory by fish on the coral Montastraea cavernosa - J. K. Jarett; D. J. Gochfeld; M. P. Lesser (Coral Reefs, 2016)

Environmental drivers of microbial community shifts in the giant barrel sponge, X estospongia muta , over a shallow to mesophotic depth gradient - Kathleen M. Morrow; Cara L. Fiore; Michael P. Lesser (Environmental Microbiology, 2016)
Summary The giant barrel sponge, X estospongia muta , is a high microbial abundance sponge found on Caribbean coral reefs along shallow to mesophotic depth gradients where multiple abiotic factors change with depth. Sponges were collected along a depth gradient at L ittle C ayman ( LC ) and Lee Stocking Island ( LSI ), and the microbiome of these samples was analysed using 16 S r RNA amplicon sequencing. Statistically significant shifts in community structure and dissimilarity (∼ 40%) were detected from 10 to 90 m in LC sponges, but a similar shift was not identified in sponges from 10 to 60 m at LSI (only 17% dissimilar). Additionally, inorganic nutrient levels steadily increased with depth at LSI but not at LC . Based on bulk stable isotopic variability, sponges collected from LC were generally more enriched in 15 N and less enriched in 13 C as depth increased, suggesting a transition from dependency on photoautotrophy to heterotrophy as depth increased. Patterns of stable isotopic enrichment were largely invariant at LSI , which is also reflected in the more stable microbial community along the depth gradient. It appears that environmental factors that change with depth may contribute to differences in X . muta microbial assemblages, demonstrating the importance of contemporaneous environmental sampling in studies of the microbiome of sponges.

Variability in chemical defense across a shallow to mesophotic depth gradient in the Caribbean sponge Plakortis angulospiculatus - Marc Slattery; Deborah J. Gochfeld; M. Cristina Diaz; Robert W. Thacker; Michael P. Lesser (Coral Reefs, 2016)

Evaluating the causal basis of ecological success within the scleractinia: an integral projection model approach - Peter J. Edmunds; Scott C. Burgess; Hollie M. Putnam; Marissa L. Baskett; Lorenzo Bramanti; Nick S. Fabina; Xueying Han; Michael P. Lesser; Joshua S. Madin; Christopher B. Wall; Denise M. Yost; Ruth D. Gates (Marine Biology, 2014)

The endosymbiotic dinoflagellates (Symbiodinium sp.) of corals are parasites and mutualists - M. P. Lesser; M. Stat; R. D. Gates (Coral Reefs, 2013)

Using energetic budgets to assess the effects of environmental stress on corals: are we measuring the right things? - M. P. Lesser (Coral Reefs, 2013)

Interactions between stressors on coral reefs: analytical approaches, re-analysis of old data, and different conclusions - M. P. Lesser (Coral Reefs, 2010)

Solving cryptogenic histories using host and parasite molecular genetics: the resolution of Littorina littorea 's North American origin - APRIL M. H. BLAKESLEE; JAMES E. BYERS; MICHAEL P. LESSER (Molecular Ecology, 2008)
Even after decades of investigation using multiple sources of evidence, the natural histories of some species remain unclear (i.e. cryptogenic). A key example is Littorina littorea , the most abundant intertidal snail in northeastern North America. Native to Europe, the snail's ecological history in North America has been debated for over 100 years with no definitive resolution. To resolve its cryptogenic status, we used molecular genetics from a novel combination of the snail and a highly associated trematode parasite, Cryptocotyle lingua . Based on mitochondrial sequences of 370 L. littorea and 196 C. lingua individuals, our results demonstrate a significant reduction in genetic diversity in North America vs. Europe, North American haplotypes nested within European haplotypes, and mean divergence estimates of ~500 years ago from Europe for both host and parasite — thus supporting a recent introduction of both host and parasite to North America from Europe. Our study therefore resolves not only a specific cryptogenic history, but it also demonstrates the success of our approach generally and could be used in resolving difficult invasion histories worldwide.

Bathymetry, water optical properties, and benthic classification of coral reefs using hyperspectral remote sensing imagery - M. P. Lesser; C. D. Mobley (Coral Reefs, 2007)

The effects of environmental factors on rainbow smelt Osmerus mordax embryos and larvae - K. M. Fuda; B. M. Smith; M. P. Lesser; B. J. Legare; H. R. Breig; R. B. Stack; D. L. Berlinsky (Journal of Fish Biology, 2007)
Experiments were conducted to identify environmental factors that influence the survival of rainbow smelt Osmerus mordax during their early life stages. Developing rainbow smelt embryos and yolk‐sac larvae were cultured under controlled conditions with different dissolved oxygen (DO; 1·09, 2·18, 4·37 and 6·55 mg l −1 , pH (4·0, 4·5, 5·0, 5·5, 6·0 and 7·0), nitrate ( 0·7, 3·6, 7·3, 14·6 and 29·2 mg l −1 ), phosphate (0·04, 0·21, 0·42, 2·08 and 4·17 mg l −1 ) and salinity (0, 5, 10, 15, 20 and 30) levels. Rainbow smelt embryos were also incubated with simulated tidal salinity fluctuations (2–28), ultraviolet radiation (irradiances of 2·8, 6·2 and 5·1 W m −2 ) and under natural conditions in two rainbow smelt spawning rivers. In the laboratory, hatch was only impaired under the lowest DO and pH conditions (0 and 13% hatch, respectively) and at highest constant salinity levels (0% hatch). Larval survival was only affected by pH levels ≤5·0. The experiment that compared hatch under natural conditions was terminated when embryos became covered with silt and fungus. These results suggest that water acidification, sediment and fungal growth may affect rainbow smelt survival during their early life stages.

Variation in sunscreen compounds (mycosporine‐like amino acids) for marine species along a gradient of ultraviolet radiation transmission within doubtful sound, New Zealand - Miles D. Lamare; Michael P. Lesser; Mike F. Barker; Thomas M. Barry; Kate B. Schimanski (New Zealand Journal of Marine and Freshwater Research, 2004)
We examined the response of four species of New Zealand marine algae ( Ecklonia radiata, Apophlaea lyallii, Rhodymenia spp., Ulva lactuca ) and a sea urchin ( Evechinus chloroticus ) to spatial variation in ultraviolet radiation (UV‐R) by examining the concentration of UV‐R absorbing compounds known as mycosporine‐like amino acids (MAAs). The purpose was to understand how, and the degree to which, local marine species could potentially respond to any future increases in incident UV‐R in the New Zealand marine environment. The research was undertaken in Doubtful Sound, where we observed a gradient of water column UV‐R transmission along the 40 km length of the fiord. We examined spatial differences in MAAs along the UV‐B gradient in the macrophytes and temporal changes in MAAs in sea urchin gonads. Among the algae, thallus MAA concentrations (nmol mg –1 protein) ranged from 12.5 to 87.8 in E. radiata , from 433.1 to 1446.4 in A. lyallii , 12.7 to 103.4 in Rhodymenia spp., but were not detected in U. lactuca . For E. chloroticus , gonadal MAA concentrations ranged from 83.9 to 224.3 nmol mg –1 protein spatially, and over the year from 1.85 to 14.12 nmol mg –1 dry weight (DW) depending on site and gametogenic cycle. Laboratory manipulations indicated that concentrations of MAAs in E. chloroticus gonads and eggs are influenced by diet. MAA concentration could be correlated with UV‐B intensities in two of the algal species. E. chloroticus MAA concentrations could also be correlated with UV‐B transmission, which we concluded was a reflection of the greater ingestion and accumulation of MAA‐rich macrophytes at those sites where higher ambient UV‐R induced greater MAA concentrations to occur in the algae. Given this, we suggest that one response of marine species to increases in UV‐B would be an increase in the synthesis and/or accumulation of MAAs for photoautotrophs and a dietary accumulation of those MAAs in E. chloroticus , an important herbivore in this system.

Green‐fluorescent proteins in Caribbean corals - Charles H. Mazel; Michael P. Lesser; Maxim Y. Gorbunov; Thomas M. Barry; Julianne H. Farrell; Kevin D. Wyman; Paul G. Falkowski (Limnology and Oceanography, 2003)
Fluorescent pigments in several Indo‐Pacific and Caribbean anthozoans have recently been identified as proteins related to the Green‐fluorescent protein (GFP) of the hydromedusa Aequorea victoria . Here we show that GFP is widely distributed in many Caribbean species. The fluorescence excitation and emission spectra for the pigment are similar to those reported elsewhere for coral and noncoral GFP and the fluorescence quantum yield is estimated to be 35%. Spectral and molecular characterization of the isolated protein clearly show it to be GFP, and laboratory and in situ fluorescence measurements and Western blot analysis show that it is widespread. Bathymetric studies of GFP content using Western blots for the ecologically important congeneric corals Montastraea faveolata and Montastraea cavernosa show that there is no significant correlation between depth and GFP concentration. Nucleotide sequence data of GFP from M. faveolata and M. cavernosa show 88.2% sequence homology with each other and 46.4% homology with A. victoria GFP, whereas the percent homology with A. victoria at the amino acid level was 31.1 and 28.4% for M. cavernosa and M. faveolata , respectively, and 82.7% with each other. Measurements of reflectance and of the excitation spectrum for chlorophyll fluorescence in GFP‐containing corals indicate that GFP absorption, emission, and reflection have negligible impact on the level of solar radiation reaching the zooxanthellae and therefore play no role in coral photosynthesis by either addition or removal of photons.

Manipulation of food and photoperiod promotes out-of-season gametogenesis in the green sea urchin, Strongylocentrotus droebachiensis : implications for aquaculture - C. W. Walker; M. P. Lesser (Marine Biology, 1998)

Oxidative stress causes coral bleaching during exposure to elevated temperatures - M. P. Lesser (Coral Reefs, 1997)

Particle clearance and selection in three species of juvenile scallops - S. E. Shumway; T. L. Cucci; M. P. Lesser; N. Bourne; B. Bunting (Aquaculture International, 1997)